given , f(x)=2*(f(x-1)+g(x-1)-1)*(f(x-1)+g(x-1)-3)+12*f(x-1)-13
g(x)=(f(x-1)+g(x-1))*(f(x-1)+g(x-1)-4)+12*g(x-1)-7
here , f(0)=2,g(0)=1
if x is given how to find f(x) and g(x) when 1<=x<=10^18 and x is an non negative integer
# | User | Rating |
---|---|---|
1 | tourist | 3856 |
2 | jiangly | 3747 |
3 | orzdevinwang | 3706 |
4 | jqdai0815 | 3682 |
5 | ksun48 | 3591 |
6 | gamegame | 3477 |
7 | Benq | 3468 |
8 | Radewoosh | 3462 |
9 | ecnerwala | 3451 |
10 | heuristica | 3431 |
# | User | Contrib. |
---|---|---|
1 | cry | 167 |
2 | -is-this-fft- | 162 |
3 | Dominater069 | 160 |
4 | Um_nik | 158 |
5 | atcoder_official | 156 |
6 | Qingyu | 155 |
7 | djm03178 | 151 |
7 | adamant | 151 |
9 | luogu_official | 150 |
10 | awoo | 147 |
Suggestion pls...........
given , f(x)=2*(f(x-1)+g(x-1)-1)*(f(x-1)+g(x-1)-3)+12*f(x-1)-13
g(x)=(f(x-1)+g(x-1))*(f(x-1)+g(x-1)-4)+12*g(x-1)-7
here , f(0)=2,g(0)=1
if x is given how to find f(x) and g(x) when 1<=x<=10^18 and x is an non negative integer
Name |
---|